2012
DOI: 10.1186/1756-0500-5-110
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of epithelial and stromal immunomodulatory signalling molecules is a prognostic indicator in breast cancer

Abstract: BackgroundThe immune system has paradoxical roles during cancer development and the prognostic significance of immune modulating factors is controversial. The aim of this study was to determine the expression of cyclooxygenase 2 (COX-2), transforming growth factor-beta (TGF- beta), interleukin-10 (IL-10) and their prognostic significance in breast cancers. Ki67 was included as a measure of growth fraction of tumor cells.MethodsOn immunohistochemical stained slides from 38 breast cancer patients, we performed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…For Ki-67 expression there was a statistically significant association with larger tumour size, histological type, mitotic index, nuclear grade, histological grade of malignancy, and the presence of lymph node metastasis. Similar results have already been described by other researchers for human and canine mammary tumours (Labelle et al, 2004;De Matos et al, 2006;Richardsen et al, 2012;Santos et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…For Ki-67 expression there was a statistically significant association with larger tumour size, histological type, mitotic index, nuclear grade, histological grade of malignancy, and the presence of lymph node metastasis. Similar results have already been described by other researchers for human and canine mammary tumours (Labelle et al, 2004;De Matos et al, 2006;Richardsen et al, 2012;Santos et al, 2013).…”
Section: Discussionsupporting
confidence: 80%
“…Although the precise function of this protein is uncertain, its tight association with the cell-cycle regulation phase and its short half-life render this protein a valid marker for the assessment of the growth fraction of neoplastic cells (Klopfleisch et al, 2011;Inwald et al, 2013;Ricciardi et al, 2015). The high Ki-67 index has been positively correlated with metastasis, death from neoplasia, low disease-free survival rates, and low overall survival rates in both humans and dogs (Labelle et al, 2004;De Matos et al, 2006;Richardsen et al, 2012;Santos et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our levels of TGFb1 and CXCR4 expression in primary fibroblasts are consistent with those found in previous studies. 14,31,32 TGFb1 has been shown to activate PI3K, leading to AKT activation in diverse cell systems. 20 We have found that TGFb1, CXCR4, and p-AKT expression in fibroblasts correlated well between primaries and the involved lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports regarding the prognostic significance of TGF-␤ expression in breast tumors (81)(82)(83). TGF-␤ expression in breast tumors may be dependent on several factors including the degree of stromal reactivity and clinical subtype (84).…”
Section: Discussionmentioning
confidence: 99%